Race under reconstruction in German cinema : Robert Stemmle's Toxi - Fenner, Angelica (German and European studies, 2011)
"Race Under Reconstruction in German Cinema investigates postwar racial formations via a pivotal West German film by one of the most popular and prolific directors of the era. The release of Robert Stemmle's Toxi (1952) coincided with the enrolment in West German schools of the first five hundred Afro-German children fathered by African-American occupation soldiers. The didactic plot traces the ideological conflicts that arise among members of a patrician family when they encounter an Afro-German child seeking adoption, herein broaching issues of integration at a time when the American civil rights movement was gaining momentum and encountering violent resistance. Perceptions of 'Blackness' in Toxi demonstrate continuities with those prevailing in Wilhelmine Germany, but also signal the influence of American social science discourse and tropes originating in icons of American popular culture, such as Uncle Tom's Cabin, Birth of a Nation, and several Shirley Temple films. By applying a Cultural Studies approach to individual film sequences, publicity photos, and press reviews, Angelica Fenner relates West German discourses around race and integration to emerging economic and political anxieties, class antagonism, and the reinstatement of conventional gender roles"--Publisher.